Encoding Cryptic Crossword Clues with TEI - Martin Holmes (Journal of the Text Encoding Initiative)
The cryptic crossword is a highly sophisticated and challenging type of intellectual puzzle that has been a daily feature of British newspapers1 for nearly a century, and yet the culture and traditions surrounding it have received little scholarly attention. This article outlines a short history of the cryptic crossword and explains how cryptic clues work. I argue that cryptic crossword clues have a great deal in common with poetry, and that we have much to learn from their structure. Many cryptic clues depend for their effect on confusing the solver through the use of overlapping syntactic and semantic hierarchies, so they serve as evidence that overlapping hierarchies are not merely an unfortunate limitation afflicting XML languages but are psychologically and linguistically real. Finally, I present a TEI schema and an approach to encoding the components of cryptic crossword clues in a way that enables algorithmic analysis of trends, features, and clue types, with a view to creating a historical corpus of encoded clues which will illuminate the evolution of the tradition.